ASSOCIATION BETWEEN INJURY AND SPORTS SPECIALIZATION AMONG FEMALE HIGH SCHOOL VOLLEYBALL PLAYERS. Issue 4 (28th April 2020) - Biese, Kevin; McGuine, Timothy; Kliethermes, Stephanie; Bell, David; Watson, Andrew; Brooks, M. Alison; Post, Eric; Lang, Pamela
Background: Volleyball participation has increased and unlike other team sports, its popularity among high school girls continues to grow. With its rise in popularity, the number of girls playing club volleyball outside of school has also grown. Sports specialization in youth athletes, or year-round intensive training in a single sport at the exclusion of others has become a concern. Overuse injuries are common among female volleyball players and specialization may be one factor that puts girls at risk of injury. Hypothesis/ Purpose: Evaluate the level of sports specialization among female high school volleyball players and examine its association with injury history. Design: Retrospective cohort study. Methods: Female students in grades 9-12 at 78 high schools who were committed to trying out for their high school volleyball team were recruited to participate in this study prior to the 2018 fall high school season. Athletes completed baseline assessments of sport related injuries within the previous 12 months. The athletes were asked to report their participation in interscholastic and club volleyball, including training volume and self-reported specialization. Finally, specialization of the athletes was determined using Jayanthi's 3-point specialization scale. Athletes who had an injury that kept them out of the first day of tryouts were excluded. Univariate and multivariate analysis was performed. Results: 2216 female high school volleyball players completed baseline evaluations (Age=15.6 ± 1.1 years old, BMI= 22.5± 3.5 kgs/m 2 ) of whom 1588 identified volleyball as their primary sport (72%). Both moderately and highly specialized volleyball athletes were about twice as likely to report a musculoskeletal injury in the previous 12 months (Moderate: OR=1.84, 95%CI=1.29-2.62; High: OR=2.30, 95%CI=1.64-3.24). Similarly, those who played club volleyball were two times more likely to report a musculoskeletal injury in the past year (OR=2.00, 95%CI=1.48-2.71). Multisport athletes were also more likely to report a previous musculoskeletal injury (OR=1.69, 85%CI=1.24-2.32). Highly specialized volleyball players were more likely to participate in club volleyball (p<0.001), summer camps (p<0.001), and participate in both club and summer camps in the same year (p<0.001). Conclusions: High school girls' volleyball players who are highly specialized were more likely to report a musculoskeletal injury in the past 12 months. Similarly, those who played club volleyball were more likely to report an injury in the past year. While sports specialization seems to be associated with increased risk of injury, it may be at least partially related to increased training volume.